Study of the Chemical Properties of Black Seed and The Bioactive Substance in its Content - Thymoquinone Antioxidant (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
Thymoquinone is a bioactive compound found in the seeds of the plant Nigella sativa, commonly known as black cumin. In the last few decades, thymoquinone has gained much attention in the field of cancer due to its potential therapeutic effects. This article aims to review the current state of knowledge regarding the properties of thymoquinone and its potential therapeutic applications. The article reviews the current scientific literature on celandine seeds, thymoquinone and its biological activity.